STEREOTIP ETNIS TIONGHOA DI BANJAR SANDAKAN, DESA SULANGAI, KECAMATAN PETANG, KABUPATEN BADUNG - Paramita, Ida Bagus Gede; Nina Marini, Komang (Maha Widya Duta: Jurnal Penerangan Agama, Pariwisata Budaya, dan Ilmu Komunikasi, 2018)
The existence of Chinese ethnicity in the midst of Balinese life is an interesting thing to learn, especially the life of Chinese ethnic in the midst of the people of Sandakan Village, Sulangai Village, Petang, Badung Regency. The ability to interact with the surrounding community and the meaning of ethnicity are important things that need to be known. The pattern of interaction can be seen from the existence of mixed marriages with the local Balinese people, and inviting each other during religious rituals. Meanwhile, the meaning of their existence is in social terms, they are involved in the customary activities of the local community. Keywords: Stereotyping, Chinese Ethnicity, Sandakan Village